Death before birth: An encounter between Prenatal Pedagogy and the Pedagogy of Death. - Serrano Manzano, Bianca Fiorella (Death Studies, 2026)
Prenatal death is shrouded in silences. One such silence is in education. The main objective of this essay is to approach the study of prenatal death from the point of view that pedagogy can and should contribute to the family, educational, health, and social spheres. The article is divided into three sections. In the first, the phenomenon of prenatal death is conceptualized and described, using a five-category classification. The second starts from the origins of pedagogy and explores its potential for the study of prenatal death by means of the Pedagogy of Death and Prenatal Pedagogy. Lastly, in the third section pedagogical principles and potential applications in different educational areas are presented. From this perspective, the article concludes that there is a need to encompass both disciplines in formal, nonformal, and informal education spaces, thereby enabling the development of more complete, complex, and conscious forms of education.